Penggunaan Bahasa Indonesia dalam Pembelajaran Matematika - Zahra Putri; Angelyca; Ika Febriana; Roberto Karlos Sinaga (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Mathematics teaching and learning faces significant challenges, including the use of language as a communication tool. So the research was carried out to determine the use and correlation of language, especially Indonesian with and in learning mathematics. The scope of this research is the use of language in mathematics and the correlation between the two. This research uses a qualitative descriptive method with literature study. From the research, it was found that language and mathematics are positively correlated and language is used to describe mathematical concepts and to explain patterns, properties and relationships between mathematical objects.